Pengaruh Akuntansi Pertanggungjawaban Terhadap Kinerja Karyawan dengan Amanah Sebagai Variabel Moderasi - Dariana, Dariana; Junaida, Siti; Ezril, Ezril; Zikri, Irawan Fakhrudin Mahali (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted to determine the effect of accountability accounting on employee performance with trust as a moderating variable at BSI KCP Hangtuah 1in Bengkalis. In this research, researchers used employee performance as a dependent variable to become a benchmark for other variables that will be examined. This research is a descriptive quantitative research that uses primary data in the form of a questionnaire distributed to 18 respondents who were then analyzed using SmartPLS. The research results show that responsibility accounting has an effect on employee performance. And when moderated by mandate, the influence of responsibility accounting on employee performance becomes stronger. This is in line with theory and previous research. What makes the difference is that the existence of the trust variable as a moderating variable greatly influences the strength of the influence of the independent variable. It is hoped that the results of this research can contribute to BSI KCP Hangtuah 1 in improving service quality and employee comfort so that employees feel very comfortable and attached to BSI KCP Hangtuah 1.